Pemberdayaan Anak-Anak Usia SD dalam Bidang Keagamaan sebagai Penunjang Kegiatan Sehari-Hari Berbasis Masjid di Desa Bandorasa Wetan Kecamatan Cilimus Kabupaten Kuningan - Ratna Purwati (Etos : Jurnal Pengabdian Masyarakat, 2020)
Efforts to empower mosques are as centers for religious activities, education and social services. But in reality, the function of a mosque with a worldly dimension does not have a maximum role in the development of the Islamic ummah and civilization. In order to preserve and develop a mosque, innovative thoughts and ideas are needed as well as the willingness of all parties, especially its managers. The main problem of this research is how to empower elementary school children in the field of mosque-based religion in Bandorasa Wetan Village, Cilimus District, Kuningan Regency. The type of research used in this thesis is qualitative research, with the aim of knowing the empowerment of elementary school children in the field of mosque-based religion in Bandorasa Wetan Village, Cilimus District, Kuningan Regency by making previous observations and collecting data as well as interviews and documentation. The results of this study explain that community empowerment at the Great Mosque of Al-Huda, Bandorasa Wetan Village is able to foster and educate the community and children through mosque committee programs developed through the religious field, namely sunset recitation culture, congregational prayer movements, socio-religious competitions. and parenting activities. The research implication is for the general chairman of the great mosque al-Huda, Cilimus District along with representatives and members of the board in maintaining the performance that has been done and developing education, religious, social activities, especially for elementary school age children as an effort to discipline themselves and teaches the virtues of the mosque. Abstrak Upaya memberdayakan masjid adalah sebagai pusat kegiatan keagamaan, pendidikan dan layanan sosial. Namun dalam kenyataannya, fungsi masjid yang berdimensi duniawiyah kurang memiliki peran yang maksimal dalam pembangunan umat dan peradaban Islam. Dalam rangka untuk melestarikan dan mengembangkan masjid kiranya diperlukan pemikiran dan gagasan inovatif dan sekaligus kemauan semua pihak terutama para pengelolanya. Pokok permasalahan penelitian ini adalah bagaimana pemberdayaan anak-anak usia SD dalam bidang keagamaan berbasis masjid di Desa Bandorasa Wetan Kecamatan Cilimus Kabupaten Kuningan. Jenis Penelitian yang digunakan dalam skripsi ini adalah penelitian kualitatif, dengan tujuan untuk mengetahui pemberdayaan anak-anak usia SD dalam bidang keagamaan berbasis masjid di Desa Bandorasa Wetan Kecamatan Cilimus Kabupaten Kuningan dengan cara melakukan observasi sebelumnya dan mengumpulkan data serta wawancara dan dokumentasi. Hasil penelitian ini menjelaskan bahwa pemberdayaan masyarakat di Masjid Besar Al-Huda Desa Bandorasa Wetan mampu membina dan mendidik masyarakat dan anak-anak melalui program-program panitia masjid yang dikembangkan melalui bidang keagamaan yaitu budaya magrib mengaji, gerakan solat berjama’ah, lomba social keagamaan dan kegiatan parenting. Implikasi penelitian adalah kepada ketua umum masjid besar al-Huda Kecamatan Cilimus beserta dengan wakil dan anggota-anggota pengurus dalam mempertahankan kinerja-kinerja yang telah dilakukan dan mengembangkan edukasi, kegiatan keagamaan, sosial, khususnya untuk anak-anak usia SD sebagai upaya pendisiplinan diri dan mengajarkan muatan keutamaan masjid.